Material identification e-platform for environmentally friendly products - Selim I., Lazarevska A. M., Kandikjan T., Sidorenko S. (Middle East Technical University, Faculty of Architecture, Department of Industrial Design, Universiteler Mahallesi Dumlupinar Bulvari No:1 06800 Çankaya, Ankara, Turkey http://id.metu.edu.tr/, 2019)
Materials selection phase plays a pivotal role in product development, which is driven by consumers’ needs and manufacturers’ requirements. Hence, material research is decisive in achieving competitiveness and success in the products market. Moreover, advances in contemporary technologies have a paramount influence on how new materials are invented and developed. New trends, lifestyles, living expectations, amended with legal requirements imposed by the government –in particular, environmental concerns of products usage and their disposal– additionally complement this process. Therefore, environmentally friendly materials are getting more attention in substituting common materials in markets that are a threat to humanity and the environment. The aim of this paper is to develop an assistive classification method that comprehends product requirements and accordingly, offers the designers substantial suggestions regarding environmentally friendly materials. The complexity of the stated problem, deriving from the conflicting requirements of the designer, consumer and manufacturer, is addressed by utilizing multi-attribute analysis. The herein proposed solution is tailored more towards industrial designers, who in principle are less familiar with material attributes, which in turn complicates the material selection process when designing for the environment.
Keywords: industrial design; product attributes; material attributes; design for environment; material information platform